2022
DOI: 10.21608/tsnj.2022.243362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Intervention program on Mothers' Knowledge, Practice and Attitudes toward Management of their Children with Epilepsy and Intellectual disability

Abstract: Background: High levels of knowledge, and practice among mothers could support the needs of their children with epilepsy and intellectual disability. The aim of this study was to assess the effect of nursing intervention program on improving mothers' knowledge, practice, and attitudes toward management of their children with epilepsy and intellectual disability. A quasi-experimental design was applied in current study. A purposive sample composed of 71 mothers was recruited from three intellectual disability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…Also, all of them were entered to custody, and the most of them didn't have nursery problems or academic problems. This finding in agreement with (Nashaat et al, 2022) who observed epilepsy occur more in boys than girls and their age group under 10 years old. Also, the results by Saleh et al (2021) found that two thirds of the children were males.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, all of them were entered to custody, and the most of them didn't have nursery problems or academic problems. This finding in agreement with (Nashaat et al, 2022) who observed epilepsy occur more in boys than girls and their age group under 10 years old. Also, the results by Saleh et al (2021) found that two thirds of the children were males.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these mothers' characteristics may reflect positively on their knowledge and practice about care for their children. These findings in line with the study conducted by Nashaat et al (2022) who reported that the highest age in the studied mothers were less than forty years and insufficient income. Also, Shahin andHussien Port Said Scientific Journal of Nursing Vol.10, No.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, these mothers' characteristics may reflect positively on their knowledge and practice about care for their children. These findings in line with the study conducted by Nashaat et al (2022) who reported that the highest age in the studied mothers were less than forty years and insufficient income. Also, Shahin and Hussien (2021) found that most of the studied mothers were with insufficient income and low level of education.…”
Section: Discussionsupporting
confidence: 93%
“…Accurate knowledge about the epilepsy impacts on children and their families, especially mothers, and the development of skills are essential elements for assisting them in becoming stronger partners in children-centered care. The challenges that epilepsy presents to a child and family include challenging treatment regimens and psychosocial comorbidities that affect day-to-day functioning, inflict a heavy financial and social load on families, and are associated with low quality of life Nashaat et al, (2022). So that the present study aimed to study effect of maternal practices on quality of life for their epileptic children.…”
Section: Discussionmentioning
confidence: 99%